1987
DOI: 10.1159/000226510
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Plasma Retinol Binding Protein Levels in Recurrence of Breast Tumors in Women

Abstract: Plasma retinol-binding protein (RBP), prealbumin, vitamin A (total) and β-carotene levels were studied in premenopausal women with node-positive breast carcinoma receiving adjuvant chemotherapy. Plasma levels were measured prior to chemotherapy and at monthly intervals during the chemotherapy course. The results showed that significantly lower RBP levels during the course of the study were associated with early tumor recurrence. Patients who maintained a disease-free status for 24 months or longer had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It is noteworthy that in the present study the serum RBP was the only parameter found to be significantly lower in breast cancer patients when compared with the healthy subjects or the patients with benign breast disease. These results are in agreement with others who found an association between low plasma RBP and recurrence of either breast cancer [30] or colorectal cancer [4] in patients receiving adjuvant chemotherapy. RBP is known to be highly sensitive to an inadequate protein intake, because of its rapid turnover rate and unusually high tryptophan content [31].…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that in the present study the serum RBP was the only parameter found to be significantly lower in breast cancer patients when compared with the healthy subjects or the patients with benign breast disease. These results are in agreement with others who found an association between low plasma RBP and recurrence of either breast cancer [30] or colorectal cancer [4] in patients receiving adjuvant chemotherapy. RBP is known to be highly sensitive to an inadequate protein intake, because of its rapid turnover rate and unusually high tryptophan content [31].…”
Section: Discussionsupporting
confidence: 93%
“…Prealbumin is considered as important as albumin in the nutritional assessment. It is of interest that serum prealbumin has been reported to reflect changes in the cancer patient's clinical status in some studies (20)(21)(22)(23). The key observations made in this study can be summarized as follows: 1) low preoperative prealbumin and albumin were associated with early disease recurrence in patients with operable colorectal cancer; 2) among various clinicopathological characteristics, only a low serum albumin was independently associated with early disease recurrence; 3) low serum prealbumin lost its significance on multivariate analysis that included serum albumin.…”
Section: Discussionmentioning
confidence: 99%
“…We found only one study that looked at the influence of retinol on breast cancer prognosis (18). The study found that in premenopausal women with node-positive breast cancer receiving adjuvant chemotherapy, significantly low levels of retinol-binding protein (RBP; also known as RBP4; ref.…”
Section: Introductionmentioning
confidence: 99%